PENGARUH LATIHAN VARIASI BOX JUMP DENGAN BOLA DIGANTUNG TERHADAP KETEPATAN SMASH PADA SISWA EKSTRAKURIKULER BOLAVOLI SMA N 1 KECAMATAN SULIKI - Nurhakim, Kevin; Donie; Umar; Rudyanto (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research is motivated by the low smash accuracy of volleyball extracurricular students at SMA N 1 Suliki District which impacts the effectiveness of attacks in matches. Smash accuracy is one of the important skills that is influenced by physical condition, motor coordination, jump timing, and the training method used. This study aims to determine the effect of box jump variation training with a hanging ball on the smash accuracy of volleyball extracurricular students at SMA N 1 Suliki District. The study used a quasi-experimental method with a One Group Pretest-Posttest Design. The study population was 18 students and a sample of 10 male students selected using a random sampling technique. The research instrument used a volleyball smash accuracy test according to Nurhasan (2001). Data analysis used descriptive statistics, Liliefors' normality test, and hypothesis testing used a t-test. The results showed an increase in the average value from 4.40 at the Pretest to 6.40 at the posttest. The results of the hypothesis testing showed a t-count of 3.08, which was greater than the t-table of 1.83 at a significance level of α = 0.05. Thus, it can be concluded that box jump variation training with a hanging ball has a significant effect on increasing the accuracy of smashes of volleyball extracurricular students at SMA N 1, Suliki District.